90.2k views
3 votes
Simplify each expression. 3a^2b^-4/12a^-2b-2

A. a^4/4b^2
B.1/4b^6
C.1/4a^-4b^2
D.a^4/4b^6

Second question is
v^3w^-3/-v^-6w^3
A.-1/-v^3
B.-v^9/-w^6
C.1/v^3
-v^9w^-6
I NEED IMMEDIATELY!! PLEASE HELP THANK YOU VERY MUUUCH

User JohnnyFun
by
5.2k points

2 Answers

1 vote

Answer:

IT'S A THEN B

Explanation:

User Norbert Willhelm
by
4.7k points
2 votes

Answer:

1) A. a^4/4b^2

2) -v^9w^-6

Explanation:

1)

given

3a^2b^-4/12a^-2b-2


(3a^2b^(-4))/(12a^(-2)b^(-2))\\\\

canceling common factor 3, we get


(a^2b^(-4))/(4a^(-2)b^(-2))


=(b^(-4)a^(2-\left(-2\right)))/(4b^(-2))
=(b^(-4)a^(2-\left(-2\right)))/(4b^(-2))


=(a^4)/(4b^(-2-\left(-4\right)))


=(a^4)/(4b^2)

2)

Given:

v^3w^-3/-v^-6w^3


=-(v^3w^(-3))/(v^(-6)w^3)\\=(w^(-3)v^(3-\left(-6\right)))/(w^3)\\=(v^9w^(-3))/(w^3)\\=(v^9)/(w^(3-\left(-3\right)))\\=-(v^9)/(w^6)\\

=-v^9w^-6 !

User Mazal
by
5.2k points